Aplikasi Test Tes IQ (Intelligence Quotient) Berbasis Web Menggunakan PHP dan MySQ - Siti Maesyaroh (JEJARING : Jurnal Teknologi dan Manajemen Informatika, 2017)
IQ test is a very important role in maximizing student achievement. These results to provideinput in determining the various kinds of education policy and as accurate data for the educationstakeholders (teachers, students, parents, etc.) in order to improve human resource capacity.Application of this IQ test is a software to perform an IQ test, which consists of the managementproblems and IQ scores, so teachers BK can directly receive the report IQ scores of students. Themethod used in this application is the method of data collection and methodology. Data collectiontechniques consisted of searching the literature data, observation and interview, while themethodology use the method waterfall approach where in it consists of system analysis, systemdesign, implementation, testing and maintenance. With the application of this web based IQ tests, isexpected to assist students in making an online IQ test and find out the level of intelligence that is inthe students.Keywords : IQ Test, Method, and Application.